2021
DOI: 10.3390/cancers13071572
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cisplatin-Induced Acute Kidney Injury: Pathological Mechanisms, Pharmacological Interventions, and Genetic Mitigations

Abstract: Administration of the chemotherapeutic agent cisplatin leads to acute kidney injury (AKI). Cisplatin-induced AKI (CIAKI) has a complex pathophysiological map, which has been linked to cellular uptake and efflux, apoptosis, vascular injury, oxidative and endoplasmic reticulum stress, and inflammation. Despite research efforts, pharmaceutical interventions, and clinical trials spanning over several decades, a consistent and stable pharmacological treatment option to reduce AKI in patients receiving cisplatin rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 315 publications
(546 reference statements)
2
134
0
Order By: Relevance
“…To mimic AKI in vitro , HK-2 cells were treated with 20 µM cisplatin (MedChemExpress) for 48 h according to previous refs. ( 8 , 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…To mimic AKI in vitro , HK-2 cells were treated with 20 µM cisplatin (MedChemExpress) for 48 h according to previous refs. ( 8 , 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to quantities of studies, apoptosis induced by TNF- α , p53, and caspase-3 [ 43 , 44 ] and inflammation induced by IL-6, TNF- α , and interleukin-1 beta (IL-1 β ) played an essential role in cisplatin-induced kidney damage [ 45 , 46 ]. It was reported that cisplatin increased the expression of proinflammatory cytokine TNF- α , which induced an exogenous apoptotic pathway through its tumor necrosis factor receptor 1 (TNFR1) [ 47 ], and TNF- α can activate proinflammatory cytokines and chemokines such as NF- κ B and trigger oxidative stress, which ultimately aggravates kidney damage [ 48 ]. The study by Xu et al also demonstrated that the expression of TNF- α further helped induce the expression of receptor-interacting protein 1 (RIP1), RIP3, and mixed lineage kinase domain-like protein (MLKL) in proximal tubular cells and enhanced the necrotic signaling pathway through positive feedback [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…UMB has also been reported as a good nephron protector when it is used in combination with cisplatin, which is one of the chemotherapeutic agents used against different cancers but with limited use given its nephrotoxicity [ 85 ]. In a mouse model of cisplatin-induced acute kidney injury (AKI), it was demonstrated that UMB reduced the nephrotoxicity associated with cisplatin use.…”
Section: Methodsmentioning
confidence: 99%